Lower verbalizability of visual stimuli modulates differences in estimates of working memory capacity between children with and without developmental language disorders. (July 2020) - Arslan, Seçkin; Broc, Lucie; Mathy, Fabien
Background and aims: Children with developmental language disorder (DLD) often perform below their typically developing peers on verbal memory tasks. However, the picture is less clear on visual memory tasks. Research has generally shown that visual memory can be facilitated by verbal representations, but few studies have been conducted using visual materials that are not easy to verbalize. Therefore, we attempted to construct non-verbalizable stimuli to investigate the impact of working memory capacity. Method and results: We manipulated verbalizability in visual span tasks and tested whether minimizing verbalizability could help reduce visual recall performance differences across children with and without developmental language disorder. Visuals that could be easily verbalized or not were selected based on a pretest with non-developmental language disorder young adults. We tested groups of children with developmental language disorder (N = 23) and their typically developing peers (N = 65) using these high and low verbalizable classes of visual stimuli. The memory span of the children with developmental language disorder varied across the different stimulus conditions, but critically, although their storage capacity for visual information was virtually unimpaired, the children with developmental language disorder still had difficulty in recalling verbalizable images with simple drawings. Also, recalling complex (galaxy) images with low verbalizability proved difficult in both groups of children. An item-based analysis on correctly recalled items showed that higher levels of verbalizability enhanced visual recall in the typically developing children to a greater extent than the children with developmental language disorder. Conclusions and clinical implication : We suggest that visual short-term memory in typically developing children might be mediated with verbal encoding to a larger extent than in children with developmental language disorder, thus leading to poorer performance on visual capacity tasks. Our findings cast doubts on the idea that short-term storage impairments are limited to the verbal domain, but they also challenge the idea that visual tasks are essentially visual. Therefore, our findings suggest to clinicians working with children experiencing developmental language difficulties that visual memory deficits may not necessarily be due to reduced non-verbal skills but may be due to the high amount of verbal cues in visual stimuli, from which they do not benefit in comparison to their peers.